Artificial Restriction DNA Cutter Using Nuclease S1 for Site‐Selective Scission of Genomic DNA. Issue 1 (5th February 2019) - Rajendran, Arivazhagan; Shigi, Narumi; Sumaoka, Jun; Komiyama, Makoto
Abstract: By combining a pair of pseudo‐complementary peptide nucleic acids (pcPNAs) with S1 nuclease, a novel tool to cut DNA at a predetermined site can be obtained. Complementary pcPNAs invade the DNA duplex and base pair to each strand of a target site, creating single‐stranded regions that are cleaved by S1 nuclease. The scission site can be freely modulated by the design of pcPNAs. This method can be used to cleave a single site in the human genome. This protocol presents experimental details for site‐selective scission using this versatile new tool. © 2019 by John Wiley & Sons, Inc.